Analysis of Carreau Shooting Distances of 6 & 7 Meters Obstacles 1 Petanque Sports Using a Biomechanics Approach - Ahmad Teguh Ramadhan; Said Junaidi; Hadi Hadi; Fajar Awang Irawan; Syahru Romadhoni; Muhammad Muhibi (Universitas Negeri Semarang, 2023)
Abstract. The importance of movement analysis that results in shooting carreau petanque a distance of 6 and 7 meters, shooting carreau is the result with the best value in the sport of petanque. This study aims to improve shooting results by analyzing the initial internal factors that affect movement. The approach and method use a descriptive approach with survey methods and quantitative data analysis using the Kinovea application software version 0.9.4. The results showed that the average SD ± shoulder joint angle, elbow joint angle, wrist joint angle, waist angle, and knee joint angle at 1) the backswing phase produced a speed of 0.85 m/s - 0.36 m/s ± 0.42 m/s - 0.19 m/s. 2) the swing phase produced a speed of 3.26 m/s – 2.81 m/s ± 0.67 m/s - 0.25 m/s. 3) the release phase produced a speed of 8.89 m/s - 8.41 m/s ± 0.75 m/s - 0.46 m/s. The conclusion is that shooting carreau at a distance of 6 and 7 meters in obstacle 1 obtained an average of the medium category with a percentage of 56.67% / 46.67%. This research suggests that it can be used as a reference for coaches in making training programs for each athlete.Abstract in Indonesia. Pentingnya analisis gerakan yang menghasilkan shooting carreau petanque jarak 6 dan 7 meter, shooting carreau merupakan hasil dengan nilai terbaik dalam cabang olahraga petanque. Penelitian ini bertujuan untuk meningkatkan hasil perolehan shooting dengan menganalisis faktor intern awal yang mempengaruhi gerakan. Pendekatan dan metode menggunakan pendekatan deskriptif dengan metode survey dan analisis data kuantitatif menggunakan softwere aplikasi kinovea versi 0.9.4. hasil penelitian menunjukkan rata-rata ± SD sudut shoulder joint, sudut elbow joint, sudut wrist joint, sudut pinggang, sudut knee joint pada 1) fase backswing menghasilkan kecepatan 0,85 m/s – 0,36 m/s ± 0,42 m/s – 0,19 m/s. 2) fase swing menghasilkan kecepatan 3,26 m/s – 2,81 m/s ± 0,67 m/s – 0,25 m/s. 3) fase release menghasilkan kecepatan 8,89 m/s – 8,41 m/s ± 0,75 m/s – 0,46 m/s. Simpulannya yaitu shooting carreau pada jarak 6 meter obstacle 1 memperoleh rata-rata kategori sedang dengan persentase 56,67% / 46,67%. Saran penelitian ini yaitu dapat digunakan untuk referensi pelatih dalam membuat program latihan pada setiap atletnya.